Numerical study of the influence of irradiation parameters on the microwave-induced stresses in granite. (April 2017) - Toifl, Michael; Hartlieb, Philipp; Meisels, Ronald; Antretter, Thomas; Kuchar, Friedemar
Highlights: 3D simulations of microwave (MW) induced stresses in granite samples are presented. Various analyses with either constant MW power or constant energy are performed. Optimum MW irradiation parameters are determined for constant energy input. It is demonstrated how rock comprising comparably weak absorbers will be damaged with microwave irradiation. Numerical results are corroborated by high-power microwave experiments. Abstract: Mechanical comminution of rocks is an energy intensive process with energy efficiency around 1%. A possible way to enhance the efficiency is the prior application of high-power microwaves. Microwave irradiation of a heterogeneous material introduces inhomogeneous electromagnetic and thermal fields which result in stresses and potentially in damage. In order to assess the industrial applicability, various 3D numerical analyses with either constant microwave power or constant energy were performed on granite samples. To this end dielectric and thermal properties were taken from measurements. For the numerical computations a realistic 3D microstructure was generated by a Voronoi tessellation algorithm. In order to calculate the electromagnetic field inside the rock sample, a finite difference time domain simulation was performed. The resulting temperature as well as stress field is evaluated in finite element analyses. The numerical results were corroborated by microwave irradiation experiments on granite samples.